2014
DOI: 10.1155/2014/401012
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mercury Exposure among Dental Health Workers in Nakhon Si Thammarat Province, Thailand

Abstract: Objectives. The main objective of this study was to assess the mercury exposure levels in dental health workers that work in dental clinics. The study evaluated the airborne and urinary mercury levels, the type of work done in the clinic, and the effect of mercury exposure on health of dental health workers. Material and Methods. A case-control study was conducted with 124 exposed and 124 matched nonexposed subjects. Personal and area samplings were conducted to quantify mercury concentrations by solid sorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
6
1
1
Order By: Relevance
“…We found no significant relations between the UMLs and age and working experience of workers. This finding was in contrast to the study of Decharat et al (2014); the reason for this discrepancy can be attributed to the low mean age of workers and the several scenarios of worker's exposure to mercury vapor after breakage of CFLs. It should also be noted that seafood consumption and determination of the UMLs is a valid index of recent exposures (Shirkhanloo et al, 2014).…”
Section: Total Umlscontrasting
confidence: 97%
See 2 more Smart Citations
“…We found no significant relations between the UMLs and age and working experience of workers. This finding was in contrast to the study of Decharat et al (2014); the reason for this discrepancy can be attributed to the low mean age of workers and the several scenarios of worker's exposure to mercury vapor after breakage of CFLs. It should also be noted that seafood consumption and determination of the UMLs is a valid index of recent exposures (Shirkhanloo et al, 2014).…”
Section: Total Umlscontrasting
confidence: 97%
“…Also, the results indicated that workers who used PPE had significantly lower UMLs than those who did not. Decharat et al (2014) also reported that dental workers handling mercury-containing amalgam who used masks and gloves had significantly lower UMLs than those who did not (Decharat et al, 2014). Also, Hansen and Danscher (1997) reported that non-use of PPE leads to the accumulation of mercury in a worker’s body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury hygiene is an important practice, as without proper mercury handling, dental personnel may suffer from varying degrees of mercury intoxication, including fatality. There are a number of studies which demonstrated significantly higher levels of urinary mercury in those who worked with dental amalgam compared to those who did not (Decharat et al, 2014;Hörsted-Bindslev, 2004;Jones, 1981). However, if dental health care workers practice good mercury hygiene, it is possible to reduce mercury body burdens to a level that does not differ significantly from those who are not occupationally exposed to mercury (Hörsted-Bindslev, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During the amalgam preparation and tooth restoration process, the mercury vapor is emitted into the air [26]. Studies that determined of mercury vapor in the air at dental clinics found that mercury vapor concentrations were higher and exceeded the baseline in all dental clinics.…”
Section: Mercury Vapour Airborne In Dental Clinics;mentioning
confidence: 99%